Koszty działalności podstawowej w warunkach klęsk żywiołowych w Nadleśnictwie Węgierska Górka - Sikora, Adam; Ukalska, Joanna (Leśne Prace Badawcze, 2014)
The aim of the study was to determine the impact of increased forest management due to natural disasters on particular core unit costs. We analysed the direct costs for the Forest District of Węgierska Górka in the years 2004–2010 based on information from the State Forests Information System (SFIS) database compared with selected forest districts within the Regional Directorate of State Forests in Cracow (RDSF). The forest districts were divided into two groups with two and six forest districts and confidence intervals around the mean were determined and the significance of linear regressions of the considered characteristics was tested. Additionally, the growth rate (decrease) of the unit cost was calculated. Our studies showed that natural disasters affect only certain unit costs regardless of the intensity of the forest management. The increase in unit costs resulted in economic losses in forest management. A full long-term analysis of the economic impact of natural disasters should be done, taking into account the cost of reforestation of destroyed areas which may become apparent only some years later.